Resin composition for damping material

By adding polymer emulsion particles with multimodal particle size distribution to the aqueous resin composition, the problem of poor drying properties of the aqueous resin composition is solved, and the low-temperature drying properties and coating film stability are improved, and energy consumption is reduced.

CN119866364APending Publication Date: 2025-04-22NIPPON SHOKUBAI CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380065995.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-16
Filing Date
2023-09-14
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The drying film-forming properties of the aqueous resin composition are slower, resulting in an increase in energy consumption and it is difficult to reduce energy consumption while maintaining vibration damping performance.

Method used

The polymer emulsion particles are added to the resin composition and there are more than 2 peaks in the particle size distribution to improve the low-temperature dryness and coating film stability.

Benefits of technology

The low-temperature drying and coating stability are improved, energy consumption during the drying process is reduced, and the performance of vibration-absorbing materials is maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005310371770000071
    Figure BDA0005310371770000071
  • Figure BDA0005310371770000081
    Figure BDA0005310371770000081
  • Figure BDA0005310371770000091
    Figure BDA0005310371770000091
Patent Text Reader

Abstract

The purpose of the present invention is to provide a resin composition for vibration damping materials, which has excellent low-temperature drying properties and coating film stability. The present invention is a resin composition for a vibration damping material, which contains polymer emulsion particles and has two or more peaks in a particle size distribution measured using a particle size distribution meter using a dynamic light scattering method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a resin composition for a vibration damping material. The resin composition for a vibration damping material of the present invention can be used particularly for vehicles. Background Art

[0002] Vibration-damping materials are materials used to prevent vibration and noise of various structures and maintain quietness. In addition to being used under the floor of a car, they are also widely used in railway vehicles, ships, airplanes, electrical equipment, building structures, construction equipment, etc. As materials used in such vibration-damping materials, molded products such as plate-shaped molded bodies or sheet-shaped molded bodies using materials having vibration-absorbing properties as raw materials have been used in the past. In addition, in recent years, from the perspective of environmental protection and labor hygiene, the release of volatile organic compounds (VOC) from solvent-based resin compositions into the atmosphere has become a problem, thereby promoting the shift to water-based resin compositions.

[0003] For example, Patent Document 1 describes a resin composition for a vibration damping material that can produce a coating film having excellent appearance and exhibiting significantly excellent vibration damping properties over a wide temperature range. The resin composition for a vibration damping material is a resin composition for a vibration damping material that includes an emulsion formed by polymerizing monomer components, and is characterized in that the composition further includes a component having a sulfosuccinic acid (salt) skeleton, and the content of the component having a sulfosuccinic acid (salt) skeleton is 50% by mass or more in 100% by mass of anionic surfactant in the composition.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2017-048364 Summary of the invention

[0007] Problems to be solved by the invention

[0008] However, the drying film-forming property of the water-based resin composition mainly depends on the evaporation rate of water, so the drying film-forming is slow compared with the solvent-based coating, and the energy consumption used during drying is large. Although the use of water-based emulsions is preferred from the perspective of VOC, from the perspective of further reducing the environmental load, water-based resin compositions that can reduce the energy consumption used during drying are required.

[0009] The present inventors have studied a resin composition for a vibration damping material that can reduce energy consumption while maintaining the performance of the resin composition for a vibration damping material, specifically, has excellent low-temperature drying properties and coating film stability.

[0010] Means for solving problems

[0011] The present inventors have conducted studies in view of the above problems and have found that a resin composition for a vibration damping material has excellent low-temperature drying properties and coating stability, thereby completing the present invention. The resin composition for a vibration damping material contains polymer emulsion particles and has two or more peaks in the particle size distribution (particle diameter distribution) measured using a particle size distribution analyzer based on a dynamic light scattering method.

[0012] Effects of the Invention

[0013] According to the present invention, a resin composition for a vibration damping material having excellent low-temperature drying properties and coating film stability can be provided. DETAILED DESCRIPTION

[0014] <Resin composition for vibration damping material>

[0015] The resin composition for a vibration damping material disclosed herein contains polymer emulsion particles.

[0016] The resin composition for vibration damping material disclosed in the present invention has two or more peaks in the particle size distribution measured by a particle size distribution measuring instrument based on a dynamic light scattering method. By having two or more peaks in the particle size distribution, it is expected that low-temperature drying properties and coating stability can be improved. In other words, as long as there are two or more peaks in the particle size distribution of the resin composition for vibration damping material disclosed in the present invention (also referred to as the particle size distribution number), there is no particular upper limit, and it is usually 10 or less, preferably 5 or less, and more preferably 2.

[0017] It is believed that the reason why the low-temperature drying property and coating stability are improved by the presence of two or more peaks in the particle size distribution is that the filling state (packing) of the particles changes by the presence of two or more components with different particle sizes, and the viscosity of the resin composition containing the polymer emulsion particles is reduced. Therefore, even if the solid content concentration of the resin composition is increased, the operability when forming the coating can be maintained, and the water content of the resin composition can be reduced, so the low-temperature drying property is excellent. In addition, since the film is formed in a densely packed state, a stable coating that is not easy to crack can be formed.

[0018] In the particle size distribution of the resin composition for a vibration damping material disclosed herein, the particle size distribution having the largest peak intensity is defined as the first peak, and the particle size distribution having the second largest peak intensity is defined as the second peak.

[0019] The particle size distribution of the resin composition for a vibration damping material disclosed herein preferably has a first peak in a range of 300 nm to 800 nm, and a second peak in a range of 50 nm to 150 nm.

[0020] In the particle size distribution of the resin composition for vibration damping material disclosed herein, the particle size at the top of the first peak (also referred to as the particle size of the first peak) is preferably in the range of 300 nm to 800 nm. The particle size at the top of the second peak (also referred to as the particle size of the second peak) is preferably in the range of 50 nm to 150 nm.

[0021] As for the particle size distribution of the polymer emulsion particles disclosed herein, the intensity ratio (volume ratio) of the first peak in the range of 300 nm to 800 nm to the second peak in the range of 50 nm to 150 nm is preferably 10:0.3 to 10:10, more preferably 10:0.5 to 10:7, and further preferably 10:0.9 to 10:4.

[0022] The total volume of the peaks below the second peak of the resin composition for vibration damping materials disclosed in the present invention is preferably 3% by volume or more, more preferably 5% by volume or more, and further preferably 8% by volume or more relative to the overall particle size distribution. The total volume ratio of the peaks below the second peak is preferably 50% by volume or less, more preferably 40% by volume or less, and further preferably 30% by volume or less. The peak below the second peak relative to the overall particle size distribution in this specification refers to the peak other than the particle size distribution (the first peak) with the largest peak intensity, and the total volume ratio of the peaks below the second peak refers to the total volume ratio of the particle size distribution other than the first peak (for example, the total volume ratio of the particle size distribution with the second peak and the third peak). It should be noted that the calculation method of the intensity ratio (volume ratio) when the peaks overlap is as follows. For example, in the case where the particle diameter of the first peak and the second peak at the vertex of the peak is less than that of the first peak, the particle diameter value at the minimum value between the first peak and the second peak is used as the threshold, the peak above the threshold is used as the first peak, and the peak below the threshold is used as the second peak, thereby determining the first peak and the second peak to calculate the intensity ratio (volume ratio).

[0023] The resin composition for vibration damping material having the above-mentioned particle size distribution can be easily obtained by adding (post-adding) an emulsifier in addition to the emulsifier used in the monomer emulsion in the polymerization process, as described below. Alternatively, it can be obtained by mixing two or more polymer emulsion particles having different particle size distributions.

[0024] In the particle size distribution of the resin composition for vibration damping material disclosed in the present invention, the molecular weight of the particles of the first peak and the particles of the second peak are preferably uniform. By making the molecular weight uniform, it can be expected that the vibration damping property will be improved. The molecular weight uniformity of the particles of the first peak and the particles of the second peak means that there are no more than two peak tops in the molecular weight measurement of the resin composition for vibration damping material, and the molecular weight distribution (Mw / Mn) is a narrow distribution of 4.5 or less. The molecular weight distribution of the resin composition for vibration damping material disclosed in the present invention is preferably 3.5 or less, and more preferably 2.5 or less.

[0025] It is considered that the vibration damping property is improved by making the molecular weights of the particles of the first peak and the particles of the second peak uniform in the particle size distribution because the mobility of the molecular chain is improved by reducing the high molecular weight component.

[0026] The resin composition for vibration damping material in which the molecular weight of the particles of the first peak and the particles of the second peak are uniform can be easily obtained by adding (post-adding) a polymerization chain transfer agent in addition to the polymerization chain transfer agent used in the monomer emulsion in the polymerization process, as described below. Alternatively, it can be obtained by mixing two or more polymer emulsion particles having different particle size distributions but uniform molecular weight.

[0027] The above-mentioned particle size distribution is measured by the method described in Examples.

[0028] (Polymer emulsion particles)

[0029] The polymer emulsion particles disclosed herein include an emulsion obtained by polymerizing monomer components, and are emulsion particles containing a polymer having a structural unit derived from the monomer. The structural unit derived from the monomer is not limited to a structural unit formed by polymerizing the monomer, and may be a structural unit formed by a post-reaction after polymerization.

[0030] The polymer disclosed in the present invention is not particularly limited, and may have a structural unit derived from a carboxylic acid (salt) group-containing monomer. The carboxylic acid (salt) group refers to a carboxylic acid group and / or a carboxylate group.

[0031] As the salt of the structural unit derived from the carboxylate group-containing monomer disclosed in the present invention, metal salts, ammonium salts, organic amine salts, etc. are preferred. As the metal atom forming the metal salt, for example, monovalent metal atoms such as alkali metal atoms such as lithium, sodium, and potassium; divalent metal atoms such as calcium and magnesium; trivalent metal atoms such as aluminum and iron are preferred. In addition, as the organic amine salt, alkanolamine salts such as ethanolamine salts, diethanolamine salts, and triethanolamine salts, and triethylamine salts are preferred.

[0032] The structural unit derived from the carboxylic acid (salt) group-containing monomer of the present disclosure is preferably a structural unit derived from a (meth)acrylic acid monomer. In other words, the polymer emulsion particles of the present disclosure preferably contain a (meth)acryl polymer. A (meth)acryl polymer refers to a polymer having a structural unit derived from a (meth)acrylic acid monomer.

[0033] As the (meth)acryl polymer disclosed in the present invention, it is preferred that the polymer comprises a structural unit derived from a (meth)acrylic acid monomer and a structural unit derived from other copolymerizable unsaturated monomers. By including a structural unit derived from a (meth)acrylic acid monomer, the dispersibility of inorganic pigments and the like in the coating material comprising the resin composition for vibration damping material of the present invention is improved, and the function of the obtained coating film is more excellent. In addition, by including other copolymerizable unsaturated monomers, it is easy to adjust the acid value, Tg, physical properties, etc. of the polymer.

[0034] The (meth)acrylic acid monomer disclosed in the present invention is a monomer having at least one of an acryloyl group or a methacryloyl group or a group in which hydrogen atoms in these groups are substituted with other atoms or atomic groups, and having a carboxyl group (—COOH group) having a carbonyl group in the group, or a salt thereof, or an acid anhydride group (—C(═O)—OC(═O)- group), preferably a (meth)acrylic acid (salt).

[0035] The salt of the carboxyl group of the (meth)acrylic acid monomer of the present disclosure is preferably a metal salt, an ammonium salt, an organic amine salt, etc. The metal salt and the organic amine salt include the same ones as those described above as the salt of the monomer unit having a carboxylate group.

[0036] As other copolymerizable unsaturated monomers disclosed in the present invention, there can be mentioned (meth)acrylic monomers other than (meth)acrylic monomers, unsaturated monomers having an aromatic ring, etc. The (meth)acrylic monomers other than the above-mentioned (meth)acrylic monomers refer to monomers having an acryloyl group or a methacryloyl group or a group in which hydrogen atoms in these groups are substituted with other atoms or atomic groups, and a carboxyl group is in the form of an ester, or a derivative of such a monomer.

[0037] Examples of the (meth)acryl monomer other than the (meth)acrylic monomer of the present disclosure include methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, isopropyl acrylate, isopropyl methacrylate, butyl acrylate, butyl methacrylate, isobutyl acrylate, isobutyl methacrylate, tert-butyl acrylate, tert-butyl methacrylate, amyl acrylate, amyl methacrylate, isoamyl acrylate, isoamyl methacrylate, hexyl acrylate, hexyl methacrylate, cyclohexyl acrylate, cyclohexyl methacrylate, octyl acrylate, octyl methacrylate, isooctyl acrylate, isooctyl methacrylate, nonyl acrylate, nonyl methacrylate, isononyl acrylate, isononyl methacrylate, decyl acrylate, decyl methacrylate, dodecyl acrylate, dodecyl methacrylate, tridecyl acrylate, methyl Tridecyl acrylate, hexadecyl acrylate, hexadecyl methacrylate, octadecyl acrylate, octadecyl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, vinyl formate, vinyl acetate, vinyl propionate, 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, diallyl phthalate, triallyl cyanurate, ethylene glycol diacrylate, ethylene glycol dimethacrylate, 1,4-butanediol diacrylate, 1,4-butanediol dimethacrylate, 1,6-hexanediol diacrylate, 1,6-hexanediol dimethacrylate, diethylene glycol diacrylate, diethylene glycol dimethacrylate, allyl acrylate, allyl methacrylate, and the like; esters of (meth)acrylic monomers other than these, and the like, are preferably used alone or in combination.

[0038] Examples of the unsaturated monomer having an aromatic ring in the present disclosure include divinylbenzene, styrene, α-methylstyrene, vinyltoluene, ethylvinylbenzene, and the like, and styrene is preferred.

[0039] The content of the structural unit derived from the (meth)acrylic acid monomer in 100 parts by mass of the (meth)acryl polymer of the present disclosure is preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, further preferably 0.5 parts by mass or more, and particularly preferably 0.7 parts by mass or more. The content of the structural unit derived from the (meth)acrylic acid monomer is preferably 5 parts by mass or less, more preferably 4 parts by mass or less, and further preferably 3 parts by mass or less.

[0040] The content of the structural unit derived from other copolymerizable unsaturated monomers in 100 parts by mass of the (meth)acryloyl polymer of the present disclosure is preferably 95 parts by mass or more, more preferably 96 parts by mass or more, and even more preferably 97 parts by mass or more. The content of the structural unit derived from other copolymerizable unsaturated monomers is preferably 99.9 parts by mass or less, more preferably 99.7 parts by mass or less, even more preferably 99.5 parts by mass or less, and particularly preferably 99.3 parts by mass or less.

[0041] The content of the structural unit derived from the (meth)acryl monomer other than the (meth)acryl monomer in 100 parts by mass of the (meth)acryl polymer of the present disclosure is preferably 20 parts by mass or more, more preferably 40 parts by mass or more, and even more preferably 60 parts by mass or more. The content of the structural unit derived from the (meth)acryl monomer other than the (meth)acryl monomer is preferably 99.9 parts by mass or less, more preferably 99.7 parts by mass or less, and even more preferably 99.5 parts by mass or less.

[0042] The content of the structural unit derived from the unsaturated monomer having an aromatic ring in 100 parts by mass of the (meth)acryl polymer of the present disclosure is preferably 1 part by mass or more, more preferably 5 parts by mass or more, further preferably 10 parts by mass or more, and may also be 20 parts by mass or more, or 40 parts by mass or more. The content of the structural unit derived from the unsaturated monomer having an aromatic ring is preferably 80 parts by mass or less, more preferably 70 parts by mass or less, and further preferably 60 parts by mass or less.

[0043] The resin composition for vibration damping material disclosed in the present invention may contain one polymer or may contain two or more polymers. When the resin composition for vibration damping material disclosed in the present invention contains two or more polymer emulsion particles disclosed in the present invention, it may be a mixture obtained by mixing (blending) two or more polymer emulsion particles, or it may be an emulsion obtained by compounding the obtained two or more polymer chains by manufacturing a substance containing two or more polymer chains in a series of manufacturing processes (such as multi-stage polymerization, etc.). In order to obtain a substance containing two or more polymer emulsion particles in a series of manufacturing processes, the manufacturing conditions such as the monomer dropping conditions can be appropriately set. The form in which the above-mentioned two or more polymer chains are compounded can be, for example, a form having a core portion and a shell portion described later.

[0044] That is, the resin composition for a vibration damping material of the present disclosure may be a composition containing single-layer polymer emulsion particles consisting only of a core portion, may be core-shell particles having a core portion and a shell portion, or may be a mixture of these.

[0045] Examples of the polymer emulsion particles of the present disclosure having a core portion and a shell portion include a configuration including two types of polymers, one of the two types of polymers forming the core portion and the other forming the shell portion.

[0046] It should be noted that, when the polymer emulsion particles of the present disclosure contain a (meth)acryl-based polymer, the (meth)acryl-based polymer is a polymer having a structural unit derived from a (meth)acrylic acid-based monomer, which means, for example, that the (meth)acrylic acid-based monomer may be contained in any one of the monomer components forming the core portion of the polymer emulsion particles and the monomer components forming the shell portion, or may be contained in both.

[0047] In the case where the polymer emulsion particles disclosed in the present invention are in the form of a composite of two or more polymer chains, it can be a form of a homogeneous structure in which one polymer chain is completely compatible with another polymer chain and cannot be distinguished from each other, or it can be a form in which they are not completely compatible and formed in an inhomogeneous form (e.g., a core-shell composite structure, a micro-region structure). Among these structures, in order to fully exert the characteristics of the polymer emulsion particles and make stable polymer emulsion particles, for example, a core-shell composite structure is preferably used. The polymer emulsion particles with a core-shell composite structure have excellent vibration damping properties in a wide range within the practical temperature range. In particular, in high temperature regions, it also exerts a vibration damping property that is superior to other forms of vibration damping material resin compositions. As a result, within the practical temperature range, it can exert vibration damping performance in a wide range from normal temperature to high temperature regions. It should be noted that in the above-mentioned core-shell composite structure, it is preferably a form in which the surface of the core is coated with the shell. In this case, the surface of the core is preferably completely coated with the shell, but it may not be completely coated, for example, it may be a form in which it is coated in a mesh shape or a form in which the core is exposed everywhere.

[0048] The polymer emulsion particles of the present disclosure may contain a compound having a sulfosuccinate (salt) skeleton in addition to the above-mentioned polymer.

[0049] The compound having a sulfosuccinic acid (salt) skeleton of the present disclosure may be a compound represented by the following general formula (1).

[0050] [Chemistry 1]

[0051]

[0052] (Where R 1 represents a hydrogen atom or a monovalent alkyl group having 1 to 30 carbon atoms. -A- represents -O- or -NH-. R 2represents an alkylene group having 1 to 30 carbon atoms. The average number of added moles n is 0 to 200. X and Y are the same or different and represent a hydrogen atom or a sulfonic acid (salt) group. At least one of X and Y represents a sulfonic acid (salt) group. R 3 A compound represented by (representing a hydrogen atom, an alkyl group, a metal salt, an ammonium salt or an organic amine salt) is preferred.

[0053] The above R 1 Preferably, it is a monovalent alkyl group having 1 to 30 carbon atoms. 1 The number of carbon atoms in is preferably 4 or more, more preferably 8 or more, and further preferably 12 or more. 1 The number of carbon atoms is preferably 25 or less, more preferably 20 or less.

[0054] In addition, the monovalent alkyl group is preferably a primary alkyl group or a secondary alkyl group.

[0055] The above R 2 It is preferably mainly composed of an alkylene group having 2 to 4 carbon atoms, such as ethylene, propylene, or butylene, and more preferably mainly composed of ethylene.

[0056] The "subject" mentioned here refers to the 2 O) n When the site is composed of two or more oxyalkylene groups, relative to all R 2 The number of presence is 50 to 100 mol%.

[0057] The above (R 2 O) n Among the parts, the above R 2 It is composed only of ethylene.

[0058] It is one of the preferred embodiments of the resin composition for vibration damping material of the present invention that the average number of added moles n is 3 to 200. From the perspective of further improving the function of the compound having a sulfosuccinate (salt) skeleton as an emulsifier and improving vibration damping properties, the average number of added moles n is more preferably 4 or more, further preferably 5 or more, further preferably 6 or more, and particularly preferably 7 or more. In addition, the average number of added moles n is more preferably 100 or less, further preferably 50 or less, further preferably 20 or less, and particularly preferably 10 or less.

[0059] The above X and Y are the same or different and represent a hydrogen atom or a sulfonic acid (salt) group. At least one of X and Y represents a sulfonic acid (salt) group. Preferably, either X or Y represents a sulfonic acid (salt) group and the other represents a hydrogen atom. That is, the polymer emulsion particles of the present disclosure may contain a sulfosuccinic acid half ester (salt) in addition to the above-mentioned polymer.

[0060] The sulfosuccinic acid half ester (salt) of the present disclosure may be a compound represented by the following general formula (2).

[0061] [Chemistry 2]

[0062]

[0063] (Where R 4 represents a secondary alkyl group having 12 to 14 carbon atoms. 5 represents a hydrogen atom, an alkyl group, a metal salt, an ammonium salt or an organic amine salt. n represents the average number of added moles.)

[0064] The preferred range of n in the above general formula (2) is the same as the preferred range of the average number of added moles n in the above formula (1).

[0065] The compound having a sulfosuccinic acid (salt) skeleton disclosed in the present invention can be used as an emulsifier when producing polymer emulsion particles.

[0066] The polymer emulsion particles of the present disclosure may contain polyoxyalkylene secondary alkyl ether in addition to the above-mentioned polymer and the compound having a sulfosuccinate (salt) skeleton.

[0067] The polyoxyalkylene secondary alkyl ether disclosed in the present invention may have one (poly)ethylene glycol chain or may have two or more (poly)ethylene glycol chains, but preferably has one (poly)ethylene glycol chain.

[0068] As the polyoxyalkylene secondary alkyl ether disclosed in the present invention, it is preferred to have an organic group having 3 or more carbon atoms. As the organic group having 3 or more carbon atoms, for example, hydrocarbon groups such as alkyl, alkenyl, and alkynyl groups having 3 or more carbon atoms can be cited, among which alkyl groups having 3 or more carbon atoms are preferred. The above-mentioned organic group may further have an alkoxy group, an aryl group, an alkyl sulfonyl group, an aryl sulfonyl group, an aryl alkyl sulfonyl group, a trialkyl silyl group, a dialkyl aryl silyl group, an alkyl diaryl silyl group, a triaryl silyl group, a bis (dialkylamino) phosphino group, a bis (dialkylamino) phosphino group, a dialkyl phosphino group, a dialkyl phosphino group, a diaryl phosphino group, and a diaryl phosphino group. The number of carbon atoms of the above-mentioned organic group (preferably a hydrocarbon group) is preferably 5 or more, more preferably 8 or more, further preferably 10 or more, and particularly preferably 12 or more. In addition, the number of carbon atoms is preferably 30 or less, more preferably 24 or less, further preferably 18 or less, and particularly preferably 14 or less.

[0069] The polyoxyalkylene secondary alkyl ether disclosed in the present invention may be a compound represented by the following general formula (3).

[0070] [Chemistry 3]

[0071]

[0072] (In the formula, m and n are each an integer greater than or equal to 0. x represents the average number of moles of ethylene oxide added, and is a number from 3 to 200.) The secondary alcohol ethoxylate represented by is preferred.

[0073] In the above general formula (3), m and n are each preferably 1 or more, more preferably 2 or more, further preferably 3 or more, and particularly preferably 4 or more. The preferred range of m+n in the above general formula (3) is as follows: m -CH-(CH2) n The total number of carbon atoms of -CH3 may be set within the preferred range of the number of carbon atoms of the organic group, preferably 2 or more, more preferably 5 or more, further preferably 7 or more, and particularly preferably 9 or more. In addition, the number of carbon atoms is preferably 27 or less, more preferably 21 or less, further preferably 15 or less, and particularly preferably 11 or less. The preferred range of x in the general formula (3) is the same as the preferred range of the average number of moles of ethylene oxide added to form the (poly)ethylene glycol chain n.

[0074] As the polyoxyalkylene secondary alkyl ether disclosed in the present invention, it is possible to obtain it by using a known method such as adding ethylene oxide or the like to the hydroxyl group possessed by the secondary alcohol. In addition, as the compound of the present invention, a commercially available product can also be used. As a commercially available product, for example, SOFTANOL 90, SOFTANOL 120, SOFTANOL 200, SOFTANOL 400, SOFTANOL M series, SOFTANOL L90, SOFTANOL L series (each manufactured by Nippon Shokubai Co., Ltd.) can be cited.

[0075] The polyoxyalkylene secondary alkyl ether disclosed in the present invention can be used as an emulsifier when preparing polymer emulsion particles.

[0076] The glass transition temperature of the polymer emulsion particles disclosed in the present invention is preferably above -20°C, more preferably above -15°C, and further preferably above -10°C. The glass transition temperature is preferably below 40°C, more preferably below 35°C, and further preferably below 30°C. The glass transition temperature of the polymer emulsion particles disclosed in the present invention refers to the glass transition temperature of the polymer forming the polymer emulsion particles. It should be noted that the glass transition temperature (Tg) can be calculated by the method described in the embodiments described below. In addition, in the case where at least one of the emulsions of the present invention is an emulsion obtained by multi-stage polymerization (for example, in the case of polymer emulsion particles having a core portion and a shell portion), the above-mentioned glass transition temperature refers to the Tg (total Tg) calculated from the monomer composition used in all stages.

[0077] When at least one of the polymer emulsion particles disclosed herein is in the form of a composite of two or more polymer chains, the glass transition temperature of one polymer chain (e.g., the polymer chain of the core) is preferably 0°C or higher, more preferably 10°C or higher. The glass transition temperature of the one polymer chain is preferably 60°C or lower, more preferably 50°C or lower. In addition, the glass transition temperature of the other polymer chain (e.g., the polymer chain of the shell) is preferably -30°C or higher, more preferably -20°C or higher. The glass transition temperature of the other polymer chain is preferably 30°C or lower, more preferably 20°C or lower. In addition, the difference in glass transition temperature between the one polymer chain and the other polymer chain is preferably 5°C or higher, more preferably 10°C or higher, and further preferably 20°C or higher. The difference in glass transition temperature is preferably 60°C or lower, more preferably 50°C or lower, and further preferably 40°C or lower. By setting the difference in glass transition temperature in this way, for example, when applied to vibration damping materials, it can be expected that higher vibration damping properties will be exhibited in a wide temperature range, and in particular, it can be expected that vibration damping properties will be further improved in the practical range of 20 to 60°C.

[0078] The weight average molecular weight of the polymer emulsion particles disclosed herein is preferably 18,000 or more, more preferably 20,000 or more, further preferably 22,000 or more, and particularly preferably 24,000 or more. The weight average molecular weight is preferably 300,000 or less, more preferably 200,000 or less, and further preferably 100,000 or less. The weight average molecular weight of the polymer emulsion particles refers to the weight average molecular weight of the polymer forming the polymer emulsion particles. It should be noted that the weight average molecular weight (Mw) can be measured using GPC under the conditions described in the examples described below.

[0079] The average particle size of the polymer emulsion particles disclosed in the present invention is preferably 80 nm or more, more preferably 100 nm or more. The average particle size is preferably 450 nm or less, more preferably 400 nm or less, and further preferably 350 nm or less. The average particle size of the polymer emulsion particles can be measured by the method described in the examples described later. By using the polymer emulsion particles having an average particle size within this range, the basic properties such as the coating appearance and coating properties required by the vibration damping material can be met, and it can be expected that the vibration damping property can be further improved.

[0080] The minimum film-forming temperature of the polymer emulsion particles disclosed herein is preferably 0° C. or higher, more preferably 5° C. or higher. The minimum film-forming temperature is preferably 40° C. or lower, more preferably 35° C. or lower, and further preferably 30° C. or lower.

[0081] Regarding the polymer emulsion particles disclosed in the present invention, from the perspective of vibration reduction design in a practical temperature range suitable for use as a vibration reduction material and improving film-forming properties during low-temperature drying, the difference between the glass transition temperature of the polymer emulsion particles and the minimum film-forming temperature of the polymer emulsion particles (|(glass transition temperature of the polymer emulsion particles) - (minimum film-forming temperature of the polymer emulsion particles)|) is preferably below 9°C, more preferably below 7°C, and even more preferably below 5°C.

[0082] The minimum film-forming temperature of the polymer emulsion particles is measured by the method described in Examples.

[0083] The polymer emulsion particles disclosed herein are preferably dispersed in a solvent, and are more preferably dispersed in an aqueous solvent from the perspective of improving the working environment. Dispersed in a solvent means that the particles are dispersed in the solvent without being dissolved.

[0084] The aqueous solvent disclosed herein may contain other organic solvents as long as it contains water, preferably water. The content of water in 100 parts by mass of the aqueous solvent is preferably 80 parts by mass or more, more preferably 90 parts by mass or more, further preferably 95 parts by mass or more, and may also be 100 parts by mass.

[0085] The content ratio of the non-volatile component of the resin composition for vibration damping material disclosed in the present invention (non-volatile component amount) is preferably 55.0% by mass or more, more preferably 57% by mass or more, and further preferably 60% by mass or more relative to the resin composition for vibration damping material. The non-volatile component amount is preferably 80% by mass or less, and may also be 70% by mass or less. It should be noted that the non-volatile component amount mentioned here can be measured using a known method. For example, about 1g of the resin composition for vibration damping material can be weighed, dried at 150°C for 1 hour with a hot air dryer, and the dried residue is taken as the non-volatile component, and the ratio relative to the mass before drying is calculated in the form of mass%.

[0086] The content of the compound having a sulfosuccinate (salt) skeleton in 100 parts by mass of the nonvolatile component of the resin composition for a vibration damping material disclosed herein is preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, further preferably 0.5 parts by mass or more, and particularly preferably 1 parts by mass or more. The content of the compound having a sulfosuccinate (salt) skeleton is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, further preferably 10 parts by mass or less, and particularly preferably 8 parts by mass or less.

[0087] The content of the sulfosuccinic acid half ester (salt) in 100 parts by mass of the nonvolatile component of the resin composition for a vibration damping material disclosed herein is preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, further preferably 0.5 parts by mass or more, and particularly preferably 1 part by mass or more. The content of the sulfosuccinic acid half ester (salt) is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, further preferably 10 parts by mass or less, and particularly preferably 8 parts by mass or less.

[0088] The content of the polyoxyalkylene secondary alkyl ether in 100 parts by mass of the nonvolatile component of the resin composition for a vibration damping material disclosed herein is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, further preferably 1 parts by mass or more, and particularly preferably 2 parts by mass or more. The content of the polyoxyalkylene secondary alkyl ether is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, further preferably 10 parts by mass or less, and particularly preferably 8 parts by mass or less.

[0089] The viscosity of the resin composition for vibration damping material disclosed in the present invention is preferably 10 mPa·s or more, more preferably 30 mPa·s or more, and further preferably 50 mPa·s or more. The viscosity is preferably 5000 mPa·s or less, more preferably 3500 mPa·s or less, and further preferably 2000 mPa·s or less. It should be noted that the viscosity of the resin composition for vibration damping material referred to here is the viscosity measured at 25°C and 20 rpm using a B-type rotational viscometer.

[0090] <Method for producing resin composition for vibration damping material>

[0091] The method for producing the resin composition for a vibration damping material of the present disclosure is not particularly limited, and is preferably produced by emulsion polymerization using an emulsifier. Methods other than emulsion polymerization may also be used, for example, a method in which an emulsifier is allowed to act on a polymer polymerized by suspension polymerization to form polymer emulsion particles.

[0092] The method for producing a resin composition for a vibration damping material disclosed herein includes, for example, a polymerization step, and the polymerization step preferably includes a step of adding an emulsifier to a reaction liquid from a monomer emulsion. In other words, the method for producing a resin composition for a vibration damping material disclosed herein may be a method for producing a resin composition for a vibration damping material having a polymerization step of performing emulsion polymerization using a monomer emulsion containing a monomer component and an emulsifier, and the polymerization step having a step of adding an emulsifier to a polymerization reaction liquid containing unreacted monomer components and an emulsifier.

[0093] By providing new micelles (reaction field of emulsion polymerization formed by an emulsifier) ​​to the unreacted monomer components, a second peak component can be generated during polymerization.

[0094] Since unreacted monomer components are essential, an emulsifier is added to the polymerization reaction liquid in the polymerization step in which a sufficient amount of unreacted monomer components remain in the polymerization reaction liquid.

[0095] There is no particular limitation on the method for conducting the emulsion polymerization disclosed herein, and for example, the method can be conducted as follows: in the presence of an emulsifier and / or a protective colloid, a monomer component and a polymerization initiator are appropriately added to an aqueous medium to conduct polymerization. In addition, in order to adjust the molecular weight, a polymerization chain transfer agent or the like is preferably used. For example, the above-mentioned polymerization step preferably includes a step of adding a polymerization chain transfer agent to a reaction solution from a monomer emulsion. In other words, the above-mentioned polymerization step preferably includes a step of adding a polymerization chain transfer agent to a polymerization reaction solution containing unreacted monomer components and an emulsifier.

[0096] It should be noted that, when the polymer contained in the polymer emulsion particles is a polymer emulsion particle having a core portion and a shell portion, it is preferably obtained by the following multi-stage polymerization: in the presence of an emulsifier and / or a protective colloid, the monomer components are emulsion polymerized in an aqueous medium to form a core portion, and then the monomer components are further emulsion polymerized in an emulsion containing the core portion to form a shell portion.

[0097] Examples of the emulsifier of the present disclosure include anionic emulsifiers, cationic emulsifiers, nonionic emulsifiers, amphoteric emulsifiers, and polymer emulsifiers, and one or more of these may be used.

[0098] The anionic emulsifier of the present invention is not particularly limited, and the above-mentioned compound having a sulfosuccinic acid (salt) skeleton is preferably used. Examples of anionic emulsifiers other than the compound having a sulfosuccinic acid (salt) skeleton include polyoxyalkylene alkyl ether sulfate ester salts, polyoxyalkylene oleyl ether sulfate sodium salts, polyoxyalkylene alkyl phenyl ether sulfate ester salts, alkyl diphenyl ether disulfonates, polyoxyalkylene (mono, di, tri) styryl phenyl ether sulfate ester salts, polyoxyalkylene (mono, di, tri) benzyl ether sulfate ester salts, Alkyl sulfonates such as alkyl phenyl ether sulfate, sodium dodecyl polyethylene glycol ether sulfate; sodium sulfonated ricinoleate; alkyl sulfonates such as sulfonated paraffin salts; alkyl sulfonates such as sodium dodecylbenzenesulfonate and alkali metal sulfate of basic phenol hydroxyethylene; high alkyl naphthalene sulfonates; naphthalenesulfonic acid formaldehyde condensate; fatty acid salts such as sodium laurate, triethanolamine oleate, and triethanolamine rosinate; polyoxyalkyl ether sulfate; polyoxyethylene carboxylate sulfate; polyoxyethylene phenyl ether sulfate; polyoxyethylene alkyl aryl sulfate, etc. One or more of them can be used.

[0099] The content of the compound having a sulfosuccinate (salt) skeleton in 100 parts by mass of the anionic emulsifier of the present disclosure is preferably 80 parts by mass or more, more preferably 90 parts by mass or more, further preferably 95 parts by mass or more, and may be 100 parts by mass.

[0100] The nonionic emulsifier disclosed in the present invention is not particularly limited, and the above-mentioned polyoxyalkylene secondary alkyl ether is preferably used. Examples of nonionic emulsifiers other than polyoxyalkylene secondary alkyl ethers include polyoxyethylene alkyl ethers; polyoxyethylene alkyl aryl ethers; sorbitan aliphatic esters; polyoxyethylene sorbitan aliphatic esters; aliphatic monoglycerides such as glycerol monolaurate; polyoxyethylene polyoxypropylene copolymers; condensation products of ethylene oxide with aliphatic amines, amides or acids, and the like.

[0101] The content of the polyoxyalkylene secondary alkyl ether in 100 parts by mass of the nonionic emulsifier of the present disclosure is preferably 80 parts by mass or more, more preferably 90 parts by mass or more, further preferably 95 parts by mass or more, and may be 100 parts by mass.

[0102] The cationic emulsifier of the present disclosure is not particularly limited, and examples thereof include dialkyldimethylammonium salts, ester-type dialkylammonium salts, amide-type dialkylammonium salts, and dialkylimidazolinium salts. One or more of these may be used.

[0103] The amphoteric emulsifier of the present disclosure is not particularly limited, and examples thereof include alkyldimethylaminoacetic acid betaine, alkyldimethylamine oxide, alkylcarboxymethylhydroxyethylimidazolinium betaine, alkylamidopropyl betaine, alkylhydroxysulfonate, and the like. One or more of these may be used.

[0104] The polymer emulsifier disclosed in the present invention is not particularly limited, and examples thereof include polyvinyl alcohol and its modified products; (meth)acryloyl water-soluble polymers; hydroxyethyl (meth)acryloyl water-soluble polymers; hydroxypropyl (meth)acryloyl water-soluble polymers; polyvinyl pyrrolidone, etc., and one or more of them can be used.

[0105] The polymerization initiator disclosed in the present invention is not particularly limited as long as it is a substance that generates free radical molecules by thermal decomposition, and preferably a water-soluble initiator is used. For example, persulfates such as potassium persulfate, ammonium persulfate, and sodium persulfate; water-soluble azo compounds such as 2,2'-azobis(2-amidinopropane) dihydrochloride and 4,4'-azobis(4-cyanovaleric acid); thermal decomposition initiators such as hydrogen peroxide; redox polymerization initiators such as hydrogen peroxide and ascorbic acid, tert-butyl hydroperoxide and Rongalite, potassium persulfate and metal salts, ammonium persulfate and sodium bisulfite, etc., and one or more of them can be used.

[0106] The amount of the polymerization initiator used in the present disclosure is not particularly limited and may be appropriately set depending on the type of the polymerization initiator, and is, for example, preferably 0.1 to 2 parts by mass, more preferably 0.2 to 1 part by mass, based on 100 parts by mass of the total amount of the monomer components for forming the polymer.

[0107] In the polymerization initiator disclosed in the present invention, a reducing agent may be used in combination as needed to promote emulsion polymerization. Examples of the reducing agent include reducing organic compounds such as ascorbic acid, tartaric acid, citric acid, and glucose; reducing inorganic compounds such as sodium thiosulfate, sodium sulfite, sodium bisulfite, sodium pyrosulfite, sodium hydrogen sulfite, and thiourea dioxide; and one or more of these can be used.

[0108] The amount of the reducing agent used in the present disclosure is not particularly limited, but is preferably 0.05 to 1 part by mass based on 100 parts by mass of the total amount of the monomer components for forming the polymer.

[0109] The mixing ratio of the polymerization initiator and the reducing agent (polymerization initiator / reducing agent) of the present disclosure is preferably 1.0 to 2.0, more preferably 1.2 to 1.9 in terms of molar ratio from the viewpoint of preventing decomposition of the isothiazolin-based compound as a surface modifier when the resin composition for a vibration damping material is prepared.

[0110] The polymerization chain transfer agent disclosed in the present invention is not particularly limited, for example, alkyl mercaptan such as hexyl mercaptan, octyl mercaptan, n-dodecyl mercaptan, tert-dodecyl mercaptan, n-hexadecyl mercaptan, and n-tetradecyl mercaptan can be cited; halogenated hydrocarbons such as carbon tetrachloride, carbon tetrabromide, and ethylene bromide; alkyl mercaptan carboxylates such as 2-ethylhexyl mercaptoacetate, 2-ethylhexyl mercaptopropionate, and tridecyl mercaptopropionate; alkyl mercaptan carboxylates such as methoxybutyl mercaptoacetate and methoxybutyl mercaptopropionate; alkyl mercaptan carboxylates such as 2-mercaptoethyl octanoate, α-methylstyrene dimer, terpinolene, α-terpinene, γ-terpinene, dipentene, anisole, allyl alcohol, etc. They can be used alone or in combination of two or more. Among these, alkyl mercaptan such as hexyl mercaptan, octyl mercaptan, n-dodecyl mercaptan, tert-dodecyl mercaptan, n-hexadecyl mercaptan, and n-tetradecyl mercaptan are preferably used.

[0111] The amount of the polymerization chain transfer agent used in the present disclosure is, for example, preferably 0.1 to 1.0% by mass, more preferably 0.3 to 0.8% by mass, based on 100% by mass of all monomer components.

[0112] Regarding the polymerization conditions such as emulsion polymerization conditions in the method for producing the resin composition for a vibration damping material disclosed herein, the polymerization temperature is not particularly limited, and is preferably 0 to 100° C., and more preferably 40 to 95° C. The polymerization time is also not particularly limited, and is preferably 1 to 15 hours, and more preferably 5 to 10 hours.

[0113] The method for adding the monomer components, polymerization initiator, etc. disclosed in the present invention is not particularly limited, and for example, a one-time addition method, a continuous addition method, a multi-stage addition method, etc. can be applied. In addition, these addition methods can also be appropriately combined.

[0114] The emulsion polymerization conditions in the method for producing the resin composition for a vibration damping material of the present disclosure may include a polymerization step of polymerizing the monomer components.

[0115] The polymerization step of the present disclosure may include an initial polymerization step, a dropping step, and an aging step after the dropping step.

[0116] The initial polymerization step of the present disclosure refers to the first step when the emulsion polymerization method is roughly divided into three steps: initial polymerization step, dropping step, and aging step, and is a step of performing polymerization for a certain period of time using a monomer emulsion containing a solvent, an emulsifier, and monomer components.

[0117] The composition of the monomer components in the initial polymerization step of the present disclosure may be any composition, and may be similar to the monomer components in the dropping step.

[0118] The monomer emulsion used in the polymerization step of the present disclosure may be added separately, or a monomer emulsion (also referred to as a pre-emulsion) containing a solvent, an emulsifier, and monomer components may be prepared and used.

[0119] The polymerization step in the method for producing the resin composition for a vibration damping material disclosed herein may include an initial polymerization step of placing a portion of the monomer emulsion into a reactor and then performing emulsion polymerization, a dropping step of dropping the remaining monomer emulsion into the polymerization reaction liquid, and an aging step of heating for a certain period of time after the dropping of the monomer emulsion is completed.

[0120] In the method for producing the resin composition for a vibration damping material disclosed in the present invention, it is preferred to include a step of adding an emulsifier separately from the emulsifier used in the monomer emulsion. By including this step, it is expected that a resin composition for a vibration damping material having two or more peaks can be easily obtained. The step of adding an emulsifier separately from the emulsifier used in the monomer emulsion is also referred to as a post-addition step of the emulsifier.

[0121] The polymerization process of the present disclosure preferably further includes a step of adding a polymerization chain transfer agent, and more preferably includes a step of adding a polymerization chain transfer agent simultaneously with the post-addition step of the emulsifier. By including this step, it can be expected that the molecular weight of particles having two or more peaks becomes uniform.

[0122] In this specification, the emulsifier used for the monomer emulsion is described as emulsifier A, and the emulsifier added separately from the emulsifier A is described as emulsifier B.

[0123] As the emulsifier A of the present disclosure, the emulsifiers described above can be used.

[0124] As the emulsifier B of the present disclosure, the above-mentioned emulsifiers can be used, and an anionic emulsifier is preferred, a compound having a sulfosuccinic acid (salt) skeleton is more preferred, and a sulfosuccinic acid half ester (salt) is further preferred.

[0125] In the method for producing the resin composition for a vibration damping material disclosed herein, the emulsifier B may be added during the dropwise addition of the monomer emulsion or after the dropwise addition is completed, and is preferably added after the dropwise addition is completed.

[0126] The emulsifier B may be added once or multiple times.

[0127] When the emulsifier B is added during the dropwise addition of the monomer emulsion, it is preferably added after the polymerization rate of the monomer emulsion exceeds 45%, more preferably after it exceeds 50%. The upper limit of the polymerization rate may be 90% or 85%.

[0128] When the emulsifier B is added during the dropwise addition of the monomer emulsion, it is preferably added for 50% or more of the total dropwise addition time of the monomer emulsion, more preferably for 60% or more, and may be 80% or more, or 90% or more.

[0129] When the emulsifier B is added after completion of the dropwise addition of the monomer emulsion, it is preferably added within 30 minutes, more preferably within 20 minutes, and even more preferably within 10 minutes.

[0130] The mass ratio of emulsifier A to emulsifier B (mass of emulsifier A / mass of emulsifier B) in the method for producing a resin composition for a vibration damping material disclosed herein is preferably 4.0 / 1.0 to 0.5 / 1.0, more preferably 3.0 / 1.0 to 0.6 / 1.0, and even more preferably 2.0 / 1.0 to 0.8 / 1.0.

[0131] In this specification, the polymerization chain transfer agent used for the monomer emulsion is described as polymerization chain transfer agent A, and the polymerization chain transfer agent added separately from the polymerization chain transfer agent A is described as polymerization chain transfer agent B.

[0132] The preferred timing, number of additions, and time of addition of the polymerization chain transfer agent B are the same as those of the emulsifier B described above.

[0133] The mass ratio of the polymer chain transfer agent A to the polymer chain transfer agent B (mass of polymer chain transfer agent A / mass of polymer chain transfer agent B) in the method for producing a resin composition for a vibration damping material disclosed herein is preferably 20.0 / 1.0 to 1.0 / 1.0, more preferably 10.0 / 1.0 to 1.5 / 1.0, and even more preferably 5.0 / 1.0 to 2.0 / 1.0.

[0134] As a method for producing the resin composition for a vibration damping material of the present disclosure, it is preferred that after producing an emulsion by emulsion polymerization, the emulsion is neutralized with a neutralizer to stabilize the emulsion.

[0135] The neutralizing agent disclosed in the present invention is not particularly limited. From the perspective of improving the water resistance of the coating formed by the resin composition for vibration damping material having a (meth)acryl polymer emulsion as an essential component, it is preferred to use a volatile base that evaporates when the coating is heated. From the perspective of good heat drying and improved vibration damping properties, it is more preferred to use an amine with a boiling point of 80 to 360°C. As such a neutralizing agent, for example, tertiary amines such as triethanolamine, 2-methylaminoethanol, dimethylethanolamine, diethylethanolamine, and morpholine, and diglycolamine are preferred. It is more preferred to use an amine with a boiling point of 130 to 280°C. It should be noted that the above boiling point is the boiling point at normal pressure.

[0136] <Coatings for vibration damping materials>

[0137] The resin composition for vibration damping material disclosed herein can be added with other components to form a paint for vibration damping material. Such a paint for vibration damping material containing the resin composition for vibration damping material as an essential component can form a vibration damping material having a coating film having excellent vibration damping properties and excellent coating film strength.

[0138] The coating material for a vibration damping material disclosed in the present invention refers to a coating material comprising at least the resin composition for a vibration damping material of the present invention and a filler.

[0139] As the filler disclosed in the present invention, for example, there can be mentioned inorganic fillers such as calcium carbonate, kaolin, silica, talc, barium sulfate, aluminum oxide, iron oxide, titanium oxide, glass powder, magnesium carbonate, aluminum hydroxide, diatomaceous earth, clay, etc.; flaky inorganic fillers such as glass flakes and mica; fibrous inorganic fillers such as metal oxide whiskers and glass fibers, etc.

[0140] When a granular filler is used as the filler of the present disclosure, the average particle size of the filler is preferably 0.5 to 50 μm, and more preferably 2 to 25 μm. Examples of the granular filler include calcium carbonate, titanium oxide, and the like.

[0141] The coating material for a vibration damping material of the present disclosure may contain other components besides the filler.

[0142] Other components included in the coating for vibration damping material disclosed herein include, for example, a foaming agent; a pigment; a thickener; a solvent; an aqueous crosslinking agent; a gelling agent; a dispersant; a defoaming agent; a colorant; an antirust pigment; a plasticizer; a stabilizer; a wetting agent; a preservative; an antifoaming agent; an anti-aging agent; an antifungal agent; an ultraviolet absorber; an antistatic agent, etc., and one or more of them can be used.

[0143] The other components of the present disclosure can be mixed with the resin composition for a vibration damping material, etc., using, for example, a butterfly mixer, a planetary mixer, a screw mixer, a kneader, a dissolver, or the like.

[0144] As the foaming agent disclosed in the present invention, for example, preferably, a heat expansion capsule containing a low boiling hydrocarbon, an organic foaming agent, an inorganic foaming agent, etc., one or more of them can be used. As the heat expansion capsule, for example, Matsumoto Microsphere F-30, F-50 (manufactured by Matsumoto Oil Co., Ltd.); Expancel WU642, WU551, WU461, DU551, DU401 (manufactured by Japan Expancel Co., Ltd.), etc., as the organic foaming agent, for example, azodicarbonamide, azobisisobutyronitrile, N,N-dinitrosopentamethylenetetramine, p-toluenesulfonylhydrazide, p-oxybis(benzenesulfonylhydrazide), etc., as the inorganic foaming agent, for example, sodium bicarbonate, ammonium carbonate, silicon hydride, etc.

[0145] Examples of the thickener of the present disclosure include polyvinyl alcohol, cellulose derivatives, and polycarboxylic acid resins.

[0146] Examples of the solvent disclosed herein include ethylene glycol, butyl cellosolve, butyl carbitol, butyl carbitol acetate, and water. The amount of the solvent blended may be appropriately set so that the nonvolatile content of the vibration damping material resin composition in the vibration damping material coating falls within the above range.

[0147] As the aqueous crosslinking agent disclosed in the present invention, for example, preferably, oxazoline compounds such as Epocros WS-500, WS-700, K-2010, 2020, and 2030 (all trade names, manufactured by Nippon Shokubai Co., Ltd.); epoxy compounds such as ADEKA Resin EMN-26-60 and EM-101-50 (all trade names, manufactured by ADEKA Co., Ltd.); melamine compounds such as Cymel C-325 (trade name, manufactured by Mitsui Cytec Co., Ltd.); blocked isocyanate compounds; zinc oxide compounds such as AZO-50 (trade name, 50% by mass zinc oxide aqueous dispersion, manufactured by Nippon Shokubai Co., Ltd.);

[0148] Examples of the gelling agent of the present disclosure include starch and agar.

[0149] Examples of the dispersant of the present disclosure include inorganic dispersants such as sodium hexametaphosphate and sodium tripolyphosphate, and organic dispersants such as polycarboxylic acid-based dispersants.

[0150] As the defoaming agent of the present disclosure, for example, a silicon-based defoaming agent or the like can be cited.

[0151] Examples of the colorant of the present disclosure include organic or inorganic colorants such as carbon black, red iron oxide, Hansa yellow, benzidine yellow, phthalocyanine blue, and quinacridone red.

[0152] Examples of the rust-preventive pigment of the present disclosure include metal phosphates, metal molybdates, metal borates, and the like.

[0153] As other components of the present disclosure, a polyvalent metal compound may also be used. In this case, the polyvalent metal compound can improve the stability, dispersibility, and heat drying properties of the coating for vibration damping materials, and the vibration damping properties of the vibration damping material formed by the coating for vibration damping materials. The polyvalent metal compound is not particularly limited, and examples thereof include zinc chloride, zinc sulfate, and the like, and one or more of them can be used.

[0154] The nonvolatile content of the vibration damping material coating disclosed herein is preferably 55% by mass or more, more preferably 65% ​​by mass or more, and further preferably 75% by mass or more, and the nonvolatile content is preferably 92% by mass or less, and may be 87% by mass or less.

[0155] The amount of the vibration damping material resin composition blended in the vibration damping material coating of the present disclosure is preferably set such that the nonvolatile content of the vibration damping material resin composition is 10 to 60% by mass, more preferably 15 to 60% by mass, based on 100% by mass of the nonvolatile content of the vibration damping material coating.

[0156] The pH of the coating material for vibration damping materials disclosed herein is preferably 7 to 11, and more preferably 7 to 9. The pH can be measured at 25°C using a pH meter ("F-23" manufactured by Horiba, Ltd.).

[0157] The blending amount of the filler of the present disclosure is preferably 50 to 700% by mass, more preferably 100 to 550% by mass, based on 100% by mass of the nonvolatile components of the resin composition for a vibration damping material.

[0158] The amount of the foaming agent in the present disclosure is preferably 0.4 to 8.0% by mass, more preferably 0.6 to 7.0% by mass, further preferably 0.8 to 6.0% by mass, and particularly preferably 1.0 to 5.0% by mass, relative to 100% by mass of the nonvolatile component of the resin composition for a vibration damping material, from the perspective of making the coating film of the vibration damping material satisfy the above-mentioned cross-sectional porosity.

[0159] The amount of the thickener of the present disclosure is preferably 0.01 to 2% by mass, more preferably 0.05 to 1.5% by mass, and even more preferably 0.1 to 1% by mass in terms of nonvolatile matter relative to 100% by mass of the nonvolatile matter of the resin composition for a vibration damping material.

[0160] The amount of the aqueous crosslinking agent of the present disclosure is preferably 0.01 to 20% by mass, more preferably 0.15 to 15% by mass, and even more preferably 0.5 to 15% by mass, based on 100% by mass of the nonvolatile components of the resin composition for a vibration damping material.

[0161] <Vibration Damping Materials>

[0162] The vibration damping material coating disclosed herein can be applied on a substrate and dried to form a coating film as a vibration damping material. The vibration damping material coating can be applied on a substrate by, for example, a brush, a scraper, air spray, airless spray, a mortar spray gun, a mortar spray gun (Lithin Gun), etc.

[0163] The average film thickness of the coating of the vibration damping material disclosed herein is preferably 1 to 5 mm. The coating of the vibration damping material of the present invention can exhibit excellent vibration damping properties regardless of its film thickness, but the average film thickness is more preferably 1.5 to 4.5 mm in terms of excellent vibration damping properties and film strength.

[0164] The average film thickness of the coating film of the present disclosure can be measured at any 10 points using a vernier caliper, and the average value thereof can be defined as the average film thickness.

[0165] In addition, it is preferred that the surface density of the coating film after drying is 1.0 to 7.0 kg / m 2The surface density is more preferably 2.0 to 6.0 kg / m 2 It should be noted that by using the coating material for a vibration damping material of the present invention, it is possible to obtain a coating film which is unlikely to expand or crack during and after drying and which is unlikely to cause the coating to slide off on an inclined surface.

[0166] The surface density of the coating film of the present disclosure can be calculated based on the coating area and the dry weight of the coated coating film.

[0167] The conditions for forming the coating film by drying after applying the vibration damping material coating disclosed in the present invention may be heating drying or room temperature drying. Since the vibration damping material coating of the present invention has excellent low temperature drying properties, it may be dried at 150°C or below, or at 130°C or below, 120°C or below, or 110°C or below. It may also be dried at 50 to 100°C.

[0168] When the resin composition for a vibration damping material or the coating material for a vibration damping material of the present disclosure is used for vibration damping material applications, the vibration damping property thereof can be evaluated by measuring the loss coefficient of a film formed from the resin composition for a vibration damping material or the coating material for a vibration damping material.

[0169] The loss factor of the present disclosure is generally represented by η, which indicates the degree of attenuation of the vibration applied to the vibration damping material. The higher the value of the loss factor, the better the vibration damping performance.

[0170] As a method for measuring the above-mentioned loss coefficient disclosed in the present invention, a resonance method for measuring near the resonance frequency is a common method, including a half-width method, an attenuation rate method, and a mechanical impedance method. In the above-mentioned resin composition for vibration damping material and the coating for vibration damping material, the loss coefficient of the film formed by the resin composition for vibration damping material and the coating for vibration damping material is preferably measured by a resonance method (3dB method) using a cantilever beam method. The measurement using the cantilever beam method can be performed, for example, using a CF-5200 FFT analyzer manufactured by Ono Sokki Co., Ltd.

[0171] The vibration damping material disclosed herein has excellent vibration damping properties and can be used in various applications. It can suppress coating film peeling and the like, and has excellent coating film strength. It can be suitably used in applications where coated vibration damping materials are used, such as automobiles, railway vehicles, ships, aircraft, electrical equipment, building structures, and construction equipment, and can be particularly suitably used in vehicle applications such as automobiles and railways.

[0172] Example

[0173] The present invention will be described in more detail below with reference to specific embodiments, but the present invention is not limited to these specific embodiments. It should be noted that, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass".

[0174] In the following Examples and Comparative Examples, various resin properties were evaluated as follows.

[0175] <Non-volatile content (NV)>

[0176] About 1 g of the obtained emulsion was weighed and dried in a hot air dryer at 150° C. for 1 hour. The dried residue was taken as a non-volatile component and the ratio relative to the mass before drying was expressed in mass %.

[0177] <Viscosity>

[0178] The viscosity was measured at 25° C. and 20 rpm using a B-type rotational viscometer (“VISCOMETER TUB-10” manufactured by Toki Sangyo Co., Ltd.).

[0179] <Average particle size>

[0180] The cumulative average particle size of the emulsion particles was measured using a particle size distribution analyzer (FPAR-1000, manufactured by Otsuka Electronics Co., Ltd.) using a dynamic light scattering method.

[0181] <Particle Size Distribution>

[0182] The particle size distribution (volume %) of the emulsion particles was measured in the range of particle sizes of 0 to 10,000 nm using a particle size distribution analyzer (LS13320 manufactured by Beckman Coulter, Inc.) using a laser diffraction scattering method.

[0183] The number of peaks of the obtained particle size distribution is defined as the particle size distribution number, and the particle size distribution with the largest peak intensity is defined as the first peak, and the particle size distribution with the second largest peak intensity is defined as the second peak. In addition, the particle size at the top of the peak in each particle size distribution is defined as the particle size of the first peak and the particle size of the second peak.

[0184] In addition, the ratio (volume %) of the total volume of the peaks following the second peak to the entire obtained particle size distribution was calculated.

[0185] <Weight average molecular weight Mw, number average molecular weight Mn>

[0186] The measurement was performed by GPC (gel permeation chromatography) under the following measurement conditions.

[0187] Measuring equipment: HLC-8120GPC (trade name, manufactured by Tosoh Corporation)

[0188] Molecular weight column: TSK-GEL GMHXL-L and TSK-GELG5000HXL (both manufactured by Tosoh Corporation) connected in series for use

[0189] Eluent: Tetrahydrofuran (THF)

[0190] Standard substance for calibration curve: Polystyrene (manufactured by Tosoh Corporation)

[0191] Measurement method: The object to be measured is dissolved in THF so that the solid content is about 0.2% by mass, and the solution is filtered through a filter. The obtained solution is used as a measurement sample, and the molecular weight is measured.

[0192] <Molecular weight distribution Mw / Mn>

[0193] The molecular weight distribution Mw / Mn was calculated by dividing the measured weight average molecular weight Mw by the number average molecular weight Mn (weight average molecular weight Mw÷number average molecular weight Mn).

[0194] <Glass transition temperature (Tg) of polymer>

[0195] The Tg of the polymer was calculated using the following calculation formula (1) from the monomer composition used in each step.

[0196] [Number 1]

[0197]

[0198] Wherein, Tg' is the Tg (absolute temperature) of the polymer. W1', W2', ... Wn' are the mass fractions of each monomer relative to all monomer components. T1, T2, ... Tn are the glass transition temperatures (absolute temperatures) of homopolymers (single polymers) formed by each monomer component.

[0199] In addition, Tg calculated from the monomer composition used in all the steps is described as "total Tg".

[0200] The Tg values ​​of the homopolymers used when calculating the glass transition temperature (Tg) of the polymerizable monomer component by the above calculation formula (1) are as follows.

[0201] Methyl methacrylate (MMA): 105°C

[0202] Styrene (St): 100°C

[0203] 2-Ethylhexyl acrylate (2EHA): -70°C

[0204] Butyl acrylate (BA): -56°C

[0205] Acrylic acid (AA): 95°C

[0206] <Minimum film forming temperature>

[0207] The minimum film-forming temperature of the emulsion was measured by applying the emulsion to a glass plate placed on a thermal gradient tester ("TP-801LT" manufactured by TESTER SANGYO) to a thickness of 0.2 mm and drying the emulsion to measure the temperature at which cracks occurred.

[0208] The surfactant used in the following examples will be described.

[0209] As the sulfosuccinic acid half ester, a compound represented by the following formula (4) (sulfosuccinic acid half ester (i)) was used.

[0210] [Chemistry 4]

[0211]

[0212] (Where R 6 represents a secondary alkyl group having 12 to 14 carbon atoms, wherein n represents the average number of added moles. )

[0213] As the polyoxyalkylene secondary alkyl ether, polyoxyethylene alkyl ether (secondary alcohol ethoxylate) manufactured by Nippon Shokubai Co., Ltd. was used, a surfactant having an EO addition mole number of 20 and an alkyl portion of secondary alcohol having 12 to 14 carbon atoms (secondary alcohol ethoxylate (ii)).

[0214] As sodium polyoxyethylene alkyl ether sulfate, Levenol WX manufactured by Kao Corporation was used.

[0215] (Example 1)

[0216] 235.0 parts of deionized water were placed in a polymerization vessel equipped with a stirrer, a reflux cooling tube, a thermometer, a nitrogen inlet tube and a dropping funnel. Then, the internal temperature was raised to 75° C. while stirring under a nitrogen stream. On the other hand, a monomer emulsion consisting of 565.0 parts of styrene, 420.0 parts of 2-ethylhexyl acrylate, 15.0 parts of acrylic acid, 6.5 parts of tert-dodecyl mercaptan (also referred to as t-DM) as a polymerization chain transfer agent, 12.1 parts of sulfosuccinic acid half ester (i) adjusted in advance to a 50% aqueous solution, 22.5 parts of secondary alcohol ethoxylate (ii) adjusted in advance to a 20% aqueous solution and 150.0 parts of deionized water was placed in the dropping funnel. Next, while the internal temperature of the polymerization vessel was maintained at 75°C, 12.0 parts of the above-mentioned monomer emulsion, 10 parts of a 2.5% ammonium persulfate aqueous solution and 10 parts of a 2% sodium bisulfite aqueous solution as a polymerization initiator (oxidant) were added to initiate initial polymerization. After 40 minutes, the remaining monomer emulsion was uniformly added dropwise over 300 minutes while the temperature in the reaction system was maintained at 75°C. At the same time, 70 parts of a 2.5% ammonium persulfate aqueous solution and 30 parts of a 2% sodium bisulfite aqueous solution were uniformly added dropwise over 300 minutes. After the addition was completed, 13.2 parts of sulfosuccinic acid half ester (i) adjusted in advance to a 50% aqueous solution was added to the reaction system. The temperature was then maintained for 120 minutes, and after the resulting reaction solution was cooled to room temperature, 18.6 parts of 2-dimethylethanolamine was added to obtain an acrylic emulsion (resin composition 1 for vibration damping material) having a glass transition temperature of 3.0°C, a non-volatile component of 64.9%, a viscosity of 541 mPa·s, an average particle size of 503 nm, and a weight-average molecular weight of 25,000.

[0217] (Example 2)

[0218] In the monomer emulsion of Example 1, the amount of styrene was changed from 565.0 parts to 505.0 parts, and the amount of 2-ethylhexyl acrylate was changed from 420.0 parts to 480.0 parts. The same operation as in Example 1 was performed except that a glass transition temperature of -7.0°C, a non-volatile component of 65.0%, a viscosity of 527 mPa·s, an average particle size of 508 nm, and a weight-average molecular weight of 25,000 were obtained.

[0219] (Example 3)

[0220] In the monomer emulsion of Example 1, the amount of styrene was changed from 565.0 parts to 620.0 parts, and the amount of 2-ethylhexyl acrylate was changed from 420.0 parts to 365.0 parts. The same operation as in Example 1 was performed except that a glass transition temperature of 13.0°C, a non-volatile component of 64.9%, a viscosity of 485 mPa·s, an average particle size of 505 nm, and a weight-average molecular weight of 25,000 were obtained.

[0221] (Example 4)

[0222] 235.0 parts of deionized water were placed in a polymerization vessel equipped with a stirrer, a reflux cooling tube, a thermometer, a nitrogen inlet tube and a dropping funnel. Then, the internal temperature was raised to 75° C. while stirring under a nitrogen stream. On the other hand, a monomer emulsion consisting of 245.0 parts of styrene, 149.0 parts of 2-ethylhexyl acrylate, 6.0 parts of acrylic acid, 2.6 parts of tert-dodecyl mercaptan (also referred to as t-DM) as a polymerization chain transfer agent, 4.8 parts of sulfosuccinic acid half ester (i) adjusted in advance to a 50% aqueous solution, 9.0 parts of secondary alcohol ethoxylate (ii) adjusted in advance to a 20% aqueous solution and 60.0 parts of deionized water was placed in the dropping funnel.

[0223] Next, while maintaining the internal temperature of the polymerization vessel at 75°C, 12.0 parts of the above-mentioned monomer emulsion, 10 parts of a 2.5% ammonium persulfate aqueous solution and 10 parts of a 2% sodium bisulfite aqueous solution as a polymerization initiator (oxidant) were added to initiate initial polymerization. After 40 minutes, the remaining monomer emulsion was uniformly added dropwise over 100 minutes while maintaining the temperature in the reaction system at 75°C. At the same time, 25 parts of a 2.5% ammonium persulfate aqueous solution and 11 parts of a 2% sodium bisulfite aqueous solution were uniformly added dropwise over 100 minutes, and the temperature was maintained for 60 minutes after the addition was completed, to obtain an aqueous dispersion of an acrylic copolymer having a glass transition temperature of 11.3°C for the core of the multilayered emulsion particles.

[0224] Next, a monomer emulsion consisting of 276.0 parts of styrene, 315.0 parts of butyl acrylate, 9.0 parts of acrylic acid, 3.9 parts of t-DM, 7.3 parts of sulfosuccinic acid half ester (i) adjusted to a 50% aqueous solution in advance, 13.5 parts of secondary alcohol ethoxylate (ii) adjusted to a 20% aqueous solution in advance, and 90.0 parts of deionized water was added to a dropping funnel, and uniformly added dropwise to the aqueous dispersion of the acrylic copolymer obtained above over 180 minutes. At the same time, 45 parts of a 2.5% ammonium persulfate aqueous solution and 19 parts of a 2% sodium bisulfite aqueous solution were uniformly added dropwise over 180 minutes. After the addition was completed, 13.2 parts of sulfosuccinic acid half ester (i) adjusted to a 50% aqueous solution in advance was added to the reaction system. The temperature was then maintained for 120 minutes to form a shell having a glass transition temperature of -2.2°C. After the obtained reaction solution was cooled to room temperature, 18.6 parts of 2-dimethylethanolamine was added to obtain an acrylic emulsion (resin composition 4 for vibration damping material) having a glass transition temperature of 3.0°C, a non-volatile content of 65.2%, a viscosity of 680 mPa·s, an average particle size of 510 nm, and a weight average molecular weight of 25,000.

[0225] (Example 5)

[0226] In the monomer emulsion of Example 1, the amount of styrene was changed from 565.0 parts to 264.5 parts, the amount of 2-ethylhexyl acrylate was changed from 420.0 parts to 228.0 parts, 264.5 parts of methyl methacrylate and 228.0 parts of butyl acrylate were further added as monomers, and 13.2 parts of sulfosuccinic acid half ester (i) added after the completion of the dropwise addition was changed to be added 270 minutes after the dropwise addition. The same operation as in Example 1 was carried out except that a glass transition temperature of 3.0°C, a non-volatile content of 65.1%, a viscosity of 857 mPa·s, an average particle size of 518 nm, and a weight average molecular weight of 25,000 were obtained.

[0227] (Example 6)

[0228] In the monomer emulsion of Example 1, the amount of tert-dodecyl mercaptan was changed from 6.5 parts to 2.0 parts. The same operation as in Example 1 was carried out except that the amount was changed from 6.5 parts to 2.0 parts, thereby obtaining an acrylic emulsion (resin composition 6 for vibration damping material) having a glass transition temperature of 3.0°C, a non-volatile component of 64.8%, a viscosity of 391 mPa·s, an average particle size of 512 nm, and a weight-average molecular weight of 200,000.

[0229] (Example 7)

[0230] The same operation as in Example 5 was performed except that 13.2 parts of sulfosuccinic acid half ester (i) added at 270 minutes of the dropwise addition was changed to 240 minutes of the dropwise addition, thereby obtaining an acrylic emulsion (resin composition 7 for vibration damping material) having a glass transition temperature of 3.0°C, a non-volatile content of 65.1%, a viscosity of 1308 mPa·s, an average particle size of 384 nm, and a weight average molecular weight of 25,000.

[0231] (Example 8)

[0232] The same operation as in Example 5 was performed except that 13.2 parts of sulfosuccinic acid half ester (i) added at 270 minutes of the dropwise addition was changed to 195 minutes of the dropwise addition, thereby obtaining an acrylic emulsion (resin composition 8 for vibration damping material) having a glass transition temperature of 3.0°C, a non-volatile content of 65.1%, a viscosity of 4020 mPa·s, an average particle size of 262 nm, and a weight average molecular weight of 25000.

[0233] (Example 9)

[0234] The same operation as in Example 1 was performed except that the amount of deionized water introduced into the polymerization vessel was changed from 235.0 parts to 365.0 parts, thereby obtaining an acrylic emulsion (resin composition 9 for vibration damping material) having a glass transition temperature of 3.0°C, a non-volatile component of 60.0%, a viscosity of 108 mPa·s, an average particle size of 507 nm, and a weight-average molecular weight of 25,000.

[0235] (Example 10)

[0236] In the monomer emulsion of Example 1, the amount of tert-dodecyl mercaptan was changed from 6.5 parts to 5.8 parts, and 0.7 parts of tert-dodecyl mercaptan was added simultaneously with 13.2 parts of sulfosuccinic acid half ester (i) added after the completion of the dropwise addition. The same operation as in Example 1 was carried out, thereby obtaining an acrylic emulsion (resin composition 10 for vibration damping material) having a glass transition temperature of 3.0°C, a non-volatile content of 65.0%, a viscosity of 498 mPa·s, an average particle size of 504 nm, and a weight average molecular weight of 23,000.

[0237] (Example 11)

[0238] In the monomer emulsion of Example 10, the amount of tert-dodecyl mercaptan was changed from 5.8 parts to 5.0 parts, and the tert-dodecyl mercaptan added after the completion of the dropwise addition was changed from 0.7 parts to 1.5 parts. The same operations as in Example 10 were performed, and an acrylic emulsion (resin composition 11 for vibration damping material) having a glass transition temperature of 3.0°C, a non-volatile component of 64.9%, a viscosity of 512 mPa·s, an average particle size of 507 nm, and a weight-average molecular weight of 21,000 was obtained.

[0239] (Example 12)

[0240] In the feeding of the monomer emulsion of Example 5, the amount of tert-dodecyl mercaptan was changed from 6.5 parts to 5.8 parts, and 0.7 parts of tert-dodecyl mercaptan was added simultaneously with 13.2 parts of sulfosuccinic acid half ester (i) added after the completion of the dropwise addition. The same operation as in Example 5 was performed except that a acrylic emulsion (resin composition 12 for vibration damping material) having a glass transition temperature of 3.0°C, a non-volatile content of 64.9%, a viscosity of 773 mPa·s, an average particle size of 521 nm, and a weight average molecular weight of 23,000 was obtained.

[0241] (Comparative Example 1)

[0242] 480.0 parts of deionized water were placed in a polymerization vessel equipped with a stirrer, a reflux cooling tube, a thermometer, a nitrogen inlet tube, and a dropping funnel. The internal temperature was then raised to 75°C while stirring under a nitrogen stream. On the other hand, a monomer emulsion consisting of 565.0 parts of styrene, 420.0 parts of 2-ethylhexyl acrylate, 15.0 parts of acrylic acid, 6.5 parts of tert-dodecyl mercaptan (also referred to as t-DM) as a polymerization chain transfer agent, 200.0 parts of sodium polyoxyethylene alkyl ether sulfate (iii) adjusted to a 20% aqueous solution in advance, and 190.0 parts of deionized water was placed in the dropping funnel. Next, while maintaining the internal temperature of the polymerization vessel at 75°C, 40.0 parts of the monomer emulsion, 10 parts of a 2.5% ammonium persulfate aqueous solution, and 10 parts of a 2% sodium bisulfite aqueous solution as a polymerization initiator (oxidant) were added to initiate initial polymerization. After 40 minutes, the remaining monomer emulsion was uniformly added dropwise over 300 minutes while the reaction system was maintained at 75°C. At the same time, 70 parts of a 2.5% aqueous solution of ammonium persulfate and 30 parts of a 2% aqueous solution of sodium bisulfite were uniformly added dropwise over 300 minutes. The temperature was then maintained for 120 minutes, and the resulting reaction solution was cooled to room temperature, followed by the addition of 18.6 parts of 2-dimethylethanolamine to obtain an acrylic emulsion (comparative resin composition 1) having a glass transition temperature of 3.0°C, a non-volatile component of 52.0%, a viscosity of 285 mPa·s, an average particle size of 150 nm, and a weight average molecular weight of 25,000.

[0243] (Comparative Example 2)

[0244] The same operation as in Example 1 was carried out except that the sulfosuccinic acid half ester (i) added after the completion of the dropping in Example 1 was not used, thereby obtaining an acrylic emulsion (comparative resin composition 2) having a glass transition temperature of 3.0°C, a non-volatile content of 65.3%, a viscosity of 11524 mPa·s, an average particle size of 701 nm, and a weight average molecular weight of 25000.

[0245] Tables 1 and 2 show the compositions of the vibration damping material resin compositions 1 to 12 described in Examples 1 to 12 and the comparative resin compositions 1 and 2 described in Comparative Examples 1 and 2, and the physical properties of the polymers.

[0246] In addition, in Examples 10 to 12, the molecular weight of the polymer was made uniform by adding a chain transfer agent together with the emulsifier.

[0247] In addition, in the following Tables 1 and 2, as described above, the particle size distribution number represents the number of peaks in the particle size distribution of the resin composition for vibration damping material measured using a particle size distribution measuring instrument based on the dynamic light scattering method. The particle size of the large particle size component represents the particle size at the top of the first peak. The particle size of the small particle size component represents the particle size at the top of the second peak. The small particle size component ratio represents the ratio of the total volume of the peaks below the second peak of the resin composition for vibration damping material to the overall particle size distribution. The degree of completion in the monomer drop time refers to the timing of adding an emulsifier, or an emulsifier and a chain transfer agent, expressed as the ratio (%) of the elapsed drop time to the total drop time of the monomer emulsion.

[0248]

[0249]

[0250] <Preparation of coating materials for vibration damping materials and coating materials of Comparative Examples 1 and 2>

[0251] Vibration damping material coatings 1 to 12 and comparative coatings 1 and 2 using the resin compositions 1 to 12 for vibration damping materials and the comparative resin compositions 1 and 2 were prepared by mixing as described below, and various properties were evaluated.

[0252] ·1000 parts by wet weight (without moisture) of the resin compositions 1 to 12 for vibration damping materials and the comparative resin compositions 1 and 2

[0253] ·Calcium carbonate NN#200 *1 1600 copies

[0254] Dispersant Aqualic DL-40S *2 20 servings

[0255] Thickener ACRYSET WR-650 *3 25 servings

[0256] Defoaming agent NOPCO 8034L *4 3 servings

[0257] Foaming agent F-30 *5 10 servings

[0258] <Preparation of coating material of Comparative Example 3>

[0259] Comparative coating material 3 as Comparative Example 3 was prepared by compounding comparative resin composition 1 as follows, and various properties were evaluated.

[0260] Comparative resin composition 1 1000 parts by wet weight (with appearance)

[0261] ·Calcium carbonate NN#200 *1 2300 copies

[0262] Dispersant Aqualic DL-40S *2 20 servings

[0263] Thickener ACRYSET WR-650 *3 25 servings

[0264] Defoaming agent NOPCO 8034L *4 3 servings

[0265] Foaming agent F-30 *5 10 servings

[0266] *1: Filler material manufactured by Nitto Powder Industry Co., Ltd.

[0267] *2: Polycarboxylic acid type dispersant manufactured by Nippon Shokubai Co., Ltd. (active ingredient 44%)

[0268] *3: Alkali-soluble acrylic thickener manufactured by Nippon Shokubai Co., Ltd. (active ingredient 30%)

[0269] *4: Defoaming agent manufactured by SAN NOPCO Co., Ltd. (Main ingredients: hydrophobic silicone + mineral oil)

[0270] *5: Foaming agent manufactured by Matsumoto Oil & Fats Co., Ltd.

[0271] <Appearance Evaluation of Coating Film>

[0272] [Evaluation of the degree of peeling, swelling and cracking of the coating film]

[0273] The prepared coating was applied to a steel plate (trade name SPCC-SD, width 75 mm × length 150 mm × thickness 0.8 mm, manufactured by Japan Testpanel Co., Ltd.) in a coating thickness of 4 mm. The coating was then dried at 110° C. for 30 minutes using a hot air dryer, and the surface state of the obtained dried coating film was evaluated by the presence or absence of peeling, swelling, and cracking.

[0274] <Evaluation of Solid Content of Coating Film>

[0275] [Evaluation of low temperature drying properties of coating films]

[0276] The initial coating solid content was calculated as a theoretical value based on the water content contained in each compound.

[0277] The prepared coating was applied to a steel plate (trade name SPCC-SD, width 75 mm × length 150 mm × thickness 0.8 mm, manufactured by Japan Testpanel Co., Ltd.) in a coating thickness of 4 mm, dried at 110°C for 30 minutes, or dried at 80°C for 30 minutes, and then left at room temperature for half a day. The solid content of the coating under each drying condition was calculated based on the reduction in moisture in the coating.

[0278] <Vibration Damping Test>

[0279] The prepared vibration damping material coating was applied to a cold-rolled steel plate (trade name SPCC, width 15 mm × length 250 mm × thickness 1.5 mm, manufactured by Japan Testpanel Co., Ltd.) with a thickness of 3 mm, pre-dried at 80°C for 30 minutes, and then dried at 150°C for 30 minutes to form a surface density of 4.0 kg / m 2 Vibration damping material coating.

[0280] Regarding the measurement of the vibration damping property, the loss coefficient at each temperature (20° C., 35° C., and 50° C.) was evaluated using the cantilever beam method (loss coefficient measurement system manufactured by Ono Sokki Co., Ltd.).

[0281] Tables 3 and 4 show various properties of the vibration damping material coating materials 1 to 12 and the comparative coating materials 1 to 3.

[0282]

[0283]

[0284] From the results of Examples 1 to 12 above, it can be seen that the resin composition for a vibration damping material containing polymer emulsion particles and having two or more peaks in the particle size distribution measured using a particle size distribution analyzer based on a dynamic light scattering method has sufficient vibration damping properties when forming a coating film, and is extremely excellent in low-temperature drying properties and coating film stability.

Claims

1. A resin composition for a vibration damping material, comprising polymer emulsion particles, wherein the composition has two or more peaks in a particle size distribution measured using a particle size distribution analyzer using a dynamic light scattering method.

2. The resin composition for a vibration damping material according to claim 1, wherein The first peak is present in the range of particle diameter of 300 nm to 800 nm, and the second peak is present in the range of particle diameter of 50 nm to 150 nm.

3. The resin composition for a vibration damping material according to claim 2, wherein The ratio of the total volume of the peaks following the second peak to the entire particle size distribution is 3% by volume or more and 50% by volume or less.

4. The resin composition for a vibration damping material according to any one of claims 1 to 3, wherein The amount of nonvolatile components is 55.0% by mass or more.

5. The resin composition for a vibration damping material according to any one of claims 1 to 4, wherein The viscosity at 25° C. is 10 mPa·s or more and 5000 mPa·s or less.

6. The resin composition for a vibration damping material according to any one of claims 1 to 5, wherein The polymer emulsion particles contain sulfosuccinic acid half ester (salt).

7. The resin composition for a vibration damping material according to claim 6, wherein The polymer emulsion particles further comprise a polyoxyalkylene secondary alkyl ether.

8. The resin composition for a vibration damping material according to any one of claims 1 to 7, wherein The weight average molecular weight of the polymer emulsion particles is greater than or equal to 18,000 and less than or equal to 300,000.

9. A method for producing a resin composition for a vibration damping material, which is a method for producing a resin composition for a vibration damping material containing polymer emulsion particles, wherein: The production method comprises a polymerization step of performing emulsion polymerization using a monomer emulsion containing a monomer component and an emulsifier. The polymerization step includes a step of adding an emulsifier to a polymerization reaction liquid containing unreacted monomer components and the emulsifier.

10. The method for producing a resin composition for a vibration damping material according to claim 9, wherein: The emulsifier added to the polymerization reaction solution is an anionic emulsifier.

11. The method for producing a resin composition for a vibration damping material according to claim 9 or 10, wherein: The mass ratio of the emulsifier contained in the monomer emulsion to the emulsifier other than the emulsifier added to the polymerization reaction solution is 4.0 / 1.0 to 0.5 / 1.

0.

12. The method for producing a resin composition for a vibration damping material according to any one of claims 9 to 11, wherein: The polymerization step includes an initial polymerization step of performing emulsion polymerization using a part of the monomer emulsion, a dropping step of dropping the remaining monomer emulsion into the polymerization reaction liquid, and an aging step after the dropping step.

13. The method for producing a resin composition for a vibration damping material according to claim 12, wherein: The step of adding the emulsifier is performed in the dropping step or the aging step.

14. The method for producing a resin composition for a vibration damping material according to any one of claims 9 to 13, wherein: The polymerization step includes a step of adding a polymerization chain transfer agent to a polymerization reaction liquid containing unreacted monomer components and an emulsifier.

15. The method for producing a resin composition for a vibration damping material according to claim 14, wherein: The monomer emulsion further comprises a polymerization chain transfer agent, The mass ratio of the polymerization chain transfer agent contained in the monomer emulsion to the polymerization chain transfer agent other than the polymerization chain transfer agent added to the polymerization reaction liquid is 20.0 / 1.0 to 1.0 / 1.0.

Citation Information

Patent Citations

  • Resin composition for vibration damping material

    JP2017048364A